1996
DOI: 10.2307/2111786
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cultural Values on Economic Development: Theory, Hypotheses, and Some Empirical Tests

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Theory: Cultural variables are incorporated into a baseline endogenous economic growth model. Hypotheses: Cultural attitudes toward achievement and thrift have a positive effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
189
0
24

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(219 citation statements)
references
References 37 publications
6
189
0
24
Order By: Relevance
“…Empirical research has demonstrated that culture can and does change (Granato et al, 1996;Jones, 2006). Moreover, cultural values are transmitted within and between generations and societies through technologies of communications, trading and immigration (Jones, 2006).…”
Section: The Link Between Cultural Values and Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical research has demonstrated that culture can and does change (Granato et al, 1996;Jones, 2006). Moreover, cultural values are transmitted within and between generations and societies through technologies of communications, trading and immigration (Jones, 2006).…”
Section: The Link Between Cultural Values and Educationmentioning
confidence: 99%
“…Recently some scholars have emphasized the need to examine the role of cultural attributes of populations as a determinant of economic growth (Greif 1994, Granato et al 1996and Swank 1996. Since Weber (1958) analyzed the linkages between the Protestant Ethic and the rise of capitalism in Europe, many scholars have investigated which cultural attitudes and beliefs facilitate economic progress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, highly professional survey organizations know how to deal with these issues and the responses can tell us quite about the values and norms that real people hold. Previous work by Granato, Inglehart & Leblang (1996) has used this approach, though with an emphasis on growth rather than levels of development. In a recent work closer to this one, Licht, Goldschmidt & Schwartz (2007) use survey data collected by Schwartz (2004) 19 to correlate cultural dimensions with "the rule of law, corruption and democratic accountability" (p. 659).…”
Section: Possibilities To Put the Theory To An Empirical Testmentioning
confidence: 99%
“…Weber (1904) was the first to point out that the two may be connected. More recently Hofstede (1980), Granato et al (1996) and Tabellini (2011), among others, document that certain cultural factors affect on economic development, over and above those due to macroeconomic or institutional factors. However, whether cultural features are related to the structure and the transmission of business cycles is, to the best of our knowledge, still a completely unexplored area.…”
Section: Introductionmentioning
confidence: 99%